Problem solving and data analysis using Minitab a clear and easy guide to six sigma methodology - Khan, Rehman M. (Wiley, 2013)
"Problem Solving and Data Analysis using Minitab presents example based learning to aid readers in understanding how to use MINITAB 16 for statistical analysis and problem solving"--